Young people's networked constructions of nature: Evidence from a qualitative multiple case study in the United Kingdom - Jack Reed; Simon Kennedy Beames; Gale Macleod (People and Nature)
Abstract How young people interpret and engage with nature is an important consideration within our current biodiversity and climate crises. What remains less clear are the ways in which online, networked, spaces underpin young people's relationships with nature, and what consequences these spaces may have for in‐person nature interactions. Given the ubiquitousness of networked spaces in society, it has been argued that day‐to‐day life is increasingly ‘postdigital’, in that we may no longer distinguish meaningful differences between our online and offline worlds. Therefore, it is necessary to examine this collapsing physical‐digital binary in the context of young people's in‐person interactions with nature to examine the effectiveness of this theoretical perspective. Utilising ethnographically situated, participant‐as‐observer methods, this qualitative multiple case study generated data across three rural residential outdoor education centres in England, Scotland and Wales, with young people aged 12–17. Participants were visiting the residential centres from urban schools in England and Scotland, with each group spending 5 days at their respective centre. Reflexive thematic analysis of fieldnote data revealed that young people had previously constructed their understandings and interpretations of what nature ‘is’ through networked environments such as Instagram, TikTok and Minecraft. These networked constructions often contextualised young people's direct, in‐person interactions with nature and demonstrated ways in which these online spaces influenced how nature was perceived and understood. The case is presented for interpreting the findings from a postdigital ‘networked baselines’ perspective. The findings will resonate with practitioners and policymakers concerned with the relationships between young people, networked spaces and nature connectedness. Alongside this, given the editorial discussion on the impacts of ‘nature on screen’ from Silk et al. (2021) in People and Nature, this paper provides a set of empirical findings on how young people's organic engagements with nature on‐screen provided a degree of foundational knowledge about what nature is, what nature is for and how nature should be engaged with. Read the free Plain Language Summary for this article on the Journal blog.